2018
DOI: 10.1021/jacs.8b09328
|View full text |Cite
|
Sign up to set email alerts
|

Roads to Rome: Role of Multiple Cassettes in Cyanobactin RiPP Biosynthesis

Abstract: Ribosomally synthesized and post-translationally modified peptides (RiPPs) are ubiquitous natural products. Bioactive RiPPs are produced from a precursor peptide, which is modified by enzymes. Usually, a single product is encoded in a precursor peptide. However, in cyanobactins and several other RiPP pathways, a single precursor peptide encodes multiple bioactive products flanking with recognition sequences known as “cassettes”. The role of multiple cassettes in one peptide is mysterious, but in general their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…As a result, in a single ORF, there are two putative core sequences rich in Ser and Cys residues separated by an "internal" leader (another leader is N-terminally located) ( Figure 8C). A similar cassette-like arrangement of core peptides has been described for several different groups of RiPPs including cyanobactins (Gu et al, 2018), thiovarsolines (Santos-Aberturas et al, 2019), orbitides (Shim et al, 2015), and dikaritins (Ding et al, 2016); but in all these cases, precursors are composed of a single leader, followed by several core peptides, interspersed by signal sequences required for the cleavage of each core at Cand N-termini by dedicated peptidases (Figure 8B shows, as an example, the sequence of TruE1 -the precursor of patellins 2 and 3, representatives of cyanobactins).…”
Section: Flavazolicinssupporting
confidence: 54%
See 2 more Smart Citations
“…As a result, in a single ORF, there are two putative core sequences rich in Ser and Cys residues separated by an "internal" leader (another leader is N-terminally located) ( Figure 8C). A similar cassette-like arrangement of core peptides has been described for several different groups of RiPPs including cyanobactins (Gu et al, 2018), thiovarsolines (Santos-Aberturas et al, 2019), orbitides (Shim et al, 2015), and dikaritins (Ding et al, 2016); but in all these cases, precursors are composed of a single leader, followed by several core peptides, interspersed by signal sequences required for the cleavage of each core at Cand N-termini by dedicated peptidases (Figure 8B shows, as an example, the sequence of TruE1 -the precursor of patellins 2 and 3, representatives of cyanobactins).…”
Section: Flavazolicinssupporting
confidence: 54%
“…These different genome arrangements from the closely related species provide a glimpse on how the genes of cassette-containing peptides may originate from an independent single short ORF through gene duplication [ Figure 8D(1)], fusion [ Figure 8D(2)], and a subsequent reduction of the role of the internal leader to that of a recognition sequence of proteases [ Figure 8D(4)]. Further multiplication of cassette-containing precursor genes may lead to arrangements found in several cyanobactin clusters [ Figure 8D(5); Gu et al, 2018]. Strikingly, only the BGCs with fused precursors contain an additional gene, which is a predicted protease (Figure 8A, orange).…”
Section: Flavazolicinsmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease in efficiency is offset by the acceptance of the increasingly structurally diversified substrate pool. Further facilitating diversity generation, these pathways do not follow a strict order of posttranslational modifications [107], which would decrease the diversity of products that can be formed. It has been suggested that these may be general features of diversity-generating biosynthetic pathways [6,108].…”
Section: Diversity-generating Biosynthesis Of Cyanobactinsmentioning
confidence: 99%
“…A strict sequence of PTM installation has been observed previously for some RiPP biosynthetic pathways such as the thiopeptides, select lanthipeptides, microcin C7, and the bottromycins . However, in other systems such as the cyanobactins, the biosynthetic enzymes have demonstrated much plasticity and can act in a variety of orders . Although we cannot rule out the possibility of strict order for the lah system, we find it unlikely that LahM1/M2 would act on a large number of previously post‐translationally modified LahA peptides.…”
Section: Resultsmentioning
confidence: 47%